Предмет: Алгебра,
автор: alinohka141
Помогите решить пожалуйста
Приложения:
Ответы
Автор ответа:
0
x²-16 - x²-14x+49 +x = (x-4)(x+4) - (x-7)² + x=
x+4 x-7 x+4 x-7
=x-4-(x-7)+x=x-4-x+7+x=x+3 =2010+3=2013
x+4 x-7 x+4 x-7
=x-4-(x-7)+x=x-4-x+7+x=x+3 =2010+3=2013
alinohka141:
спасибо
Похожие вопросы
Предмет: Українська мова,
автор: STALINANAVASNET
Предмет: Русский язык,
автор: Нетуника193
Предмет: Українська мова,
автор: riunia345p0mv5o
Предмет: Алгебра,
автор: superkt667
Предмет: Математика,
автор: tatti85